PK/PD integration of florfenicol alone and in combination with doxycycline against Riemerella anatipestifer - Zhang, Huilin; Huang, Yingxin; Yu, Jiao; Liu, Xujing; Ding, Huanzhong (Frontiers in Veterinary Science, 2022)
Riemerella anatipestifer (RA) is an important pathogen found in poultry. RA infection can kill ducks and lead to significant economic losses. Seven RA strains with different susceptibility phenotypes were chosen to study the pharmacokinetic/pharmacodynamic (PK/PD) integration of florfenicol (FF) alone and in combination with doxycycline (DOX). The checkerboard assay indicated that synergy [fractional inhibitory concentration index (FICI) ≤0.5] was detected in the CVCC3952 strain of RA and that additivity (FICI >0.5 to ≤1) was observed in other strains. Static time–kill curves showed that the bactericidal effect of FF against RA was produced at a FF concentration ≥4 MIC, and the antibacterial activity of FF against RA was enhanced from the aspects of efficacy and efficacy in combination with DOX. Dynamic time–kill curves indicated that FF elicited bactericidal activity against the CVCC3857 strain with a reduction ≥4.88 log10CFU/mL when the dose was ≥8 mg/L. However, a bactericidal effect was not achieved at the maximum administered dose of FF monotherapy (20 mg/L) for isolates with a MIC ≥4 μg/mL. The effect of FF against RA was enhanced upon combination with DOX. The combination of FF with DOX reduced the bacterial burden ≥4.53 log10CFU/mL for all strains with a MIC ≥4 μg/mL. Data were fitted to a sigmoidal Emax model. The PK/PD parameters of AUC24 h/MIC (the area under the concentration–time curve over 24 h divided by the MIC) and %T >MIC (the cumulative percentage of time over a 24-h period at which the concentration exceeded the MIC) of FF for eliciting a reduction of 3 log10CFU/mL was 40.10 h and 58.71, respectively. For strains with a MIC ≤16 μg/mL, the magnitude of the AUC24 h/MIC and Cmax/MIC required for a 3 log10CFU/mL of bacterial killing was 34.84 h and 4.74 in the presence of DOX at 0.5 MIC, respectively. These data suggest that combination of FF with DOX enhanced the activity against RA strains with various susceptibilities to FF and DOX.